Chironomid (Insecta: Diptera) assemblages along an Andean altitudinal gradient - Scheibler, Erica Elizabeth (2014)
Chironomidae are an abundant, diverse and ecologically important group common in mountain streams worldwide, but their patterns of distribution have been poorly described for the Andes region in western-central-Argentina. Here we examine chironomid assemblages along an altitudinal gradient in the Mendoza River basin to study how spatial and seasonal variations affect the abundance patterns of genera across a gradient of elevation, assess the effects of environmental variables on the chironomid community and describe its diversity using rarefaction and Shannon?s indices. Three replicate samples and physicochemical parameters were measured seasonally at 11 sites in 2000 and 2001. Twelve genera of chironomid larvae were identified, which belonged to 5 subfamilies. Chironomid composition changed from the headwaters to the outlet and was associated with changes in altitude, water temperature, substrate size and conductivity. We found a pronounced seasonal and spatial variation in the macroinvertebrate community and in physicochemical parameters. Environmental conditions such as elevated conductivity levels, and increased river discharge occurring during the summer produced low chironomid density values at the sampling sites. The rarefaction index revealed that the sampling sites with highest richness were LU (middle section of the river) and PO (lower section). Shannon?s diversity index showed LU to be the site with the lowest diversity as a consequence of the dominance of Cricotopus over the other genera found. We attribute the low diversity found in our aquatic system to the aridity of the sampling area, as has been demonstrated in studies of other similar lotic systems in this mountain region.